RELIGIOUS RADICALISM FRAME IN THE ONLINE MEDIA NEWS (Framing Analysis Reporting Of “ISIS” In Republika.co.id and Tempo.co) - Mohammad Zamroni; Yanti Dwi Astuti; Achmad Zuhri (Universitas Islam Negeri Ar-Raniry, 2021)
This study aims to explore how the framing of Islamic radicalism through the reporting of the group